KORELASI PENGETAHUAN DAN SIKAP KADER KESEHATAN DENGAN PENEMUAN SUSPEK TUBERKULOSIS PARU DI PUSKESMAS SENARU LOMBOK UTARA - Robiatul Adawiyah; Rahmani Ramli; Khairul Fuadi (PrimA: Jurnal Ilmiah Ilmu Kesehatan, 2024)
In West Nusa Tenggara, there were 33,195 suspected TB cases out of a target of 95,774 (NTB Health Office, 2021). The presence of community health volunteers (Kader)  is strategic in identifying pulmonary TB suspects, but many volunteers lack sufficient knowledge about the disease. Additionally, their attitudes and motivation are not optimal, as their participation is often voluntary. This study aims to determine the relationship between the knowledge and attitudes of health volunteers and the identification of pulmonary tuberculosis suspects at Senaru Health Center, North Lombok. This research used a correlational study design with a cross-sectional approach, using Probability Sampling (Simple Random Sampling) with a sample size of 167 people's. The instrument used in this study is a questionnaire that assesses the knowledge and attitudes of volunteers at Senaru Health Center, North Lombok Regency. The results show that 52.7% of health volunteers have good knowledge, while their attitudes are generally high. The Spearman Rho test results indicate a significant relationship between the knowledge level of health volunteers and the identification of pulmonary TB suspects (p = 0.004 < 0.05). Similarly, there is a significant relationship between the attitudes of health volunteers and the identification of pulmonary TB suspects (p = 0.007 < 0.05). The conclusion of this study is that there is a relationship between the knowledge and attitudes of health volunteers and the identification of pulmonary TB suspects at Senaru Health Center, North Lombok.